Adverse perinatal outcomes associated with antiretroviral therapy in women living with HIV: A systematic review and meta-analysis - Portwood, Clara; Sexton, Harriet; Kumarendran, Mary; Brandon, Zoe; Kirtley, Shona; Hemelaar, Joris (Frontiers in Medicine, 2023)
Background Maternal HIV infection is associated with an increased risk of adverse perinatal outcomes. The World Health Organisation (WHO) recommends immediate initiation of lifelong antiretroviral therapy (ART) for all people living with HIV, including pregnant women living with HIV (WLHIV). We aimed to assess the risk of adverse perinatal outcomes in WLHIV receiving ART compared to ART-naïve WLHIV and HIV-negative women. Methods We conducted a systematic literature review by searching PubMed, CINAHL, Global Health, and EMBASE for studies published between Jan 1, 1980, and April 20, 2020. Two investigators independently selected relevant studies and extracted data from studies reporting on the association of pregnant WLHIV receiving ART with adverse perinatal outcomes. Perinatal outcomes examined were preterm birth (PTB), very PTB, spontaneous PTB (sPTB), low birth weight (LBW), very LBW (VLBW), term LBW, preterm LBW, small for gestational age (SGA), very SGA (VSGA), stillbirth, and neonatal death. Random-effects meta-analyses examined the risk of adverse perinatal outcomes in WLHIV receiving ART compared to ART-naïve WLHIV and HIV-negative women. Subgroup and sensitivity analyses were performed based on country income status and study quality, and adjustment for confounding factors assessed. The study was registered with PROSPERO: CRD42021248987. Results Of 94,594 studies identified, 73 cohort studies, including 424,277 pregnant women, met the inclusion criteria. We found that WLHIV receiving ART are associated with a significantly decreased risk of PTB (relative risk 0.79, 95%CI 0.67-0.93), sPTB (0.46, 0.32-0.66), LBW (0.86, 0.79-0.93), and VLBW (0.62, 0.39-0.97) compared to ART-naïve WLHIV. However, WLHIV receiving ART are associated with a significantly increased risk of PTB (1.42, 1.28-1.57), sPTB (2.20, 1.32-3.67), LBW (1.58, 1.36-1.84), term LBW (1.88, 1.23-2.85), SGA (1.69, 1.32-2.17), and VSGA (1.22, 1.10-1.34) compared to HIV-negative women. Conclusion ART reduces the risk of adverse perinatal outcomes in pregnant WLHIV, but the risk remains higher than in HIV-negative women. Our findings support the WHO recommendation of immediate initiation of lifelong ART for all people living with HIV, including pregnant WLHIV.